2021
DOI: 10.1177/15274764211014580
|View full text |Cite
|
Sign up to set email alerts
|

Netflix in Europe: Four Markets, Four Platforms? A Comparative Analysis of Audio-Visual Offerings and Investment Strategies in Four EU States

Abstract: In the context of Netflix’s rapid expansion in European markets and its growing investments in original content, this article conducts a comparative case study analysis of Netflix offerings and investment strategies in four European Union countries: Belgium, Romania, Spain, and Sweden. A first aim of the article is to establish the extent to which offerings in these markets confirm or reshape the findings of transnational flow studies on the imbalance of content supply. A second aim is to analyze how these off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…This is facilitated by a combination of factors, including the platform’s global reach and business strategy (Aguiar and Waldfogel, 2018), as well as the content’s transnational appeal, its aggressive promotion of premium offerings, and its dubbing and subtitling services (Albornoz and García Leiva, 2021; Lobato, 2019). Moreover, although investments in European content have notably grown over the years, recent research has shown that the volume of ‘original’ content produced outside of the US is still limited compared to US investments, pointing to Netflix’s transnationalisation strategy as a business endeavour meant to use localised content to penetrate new markets (Albornoz and García Leiva, 2021; Iordache, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is facilitated by a combination of factors, including the platform’s global reach and business strategy (Aguiar and Waldfogel, 2018), as well as the content’s transnational appeal, its aggressive promotion of premium offerings, and its dubbing and subtitling services (Albornoz and García Leiva, 2021; Lobato, 2019). Moreover, although investments in European content have notably grown over the years, recent research has shown that the volume of ‘original’ content produced outside of the US is still limited compared to US investments, pointing to Netflix’s transnationalisation strategy as a business endeavour meant to use localised content to penetrate new markets (Albornoz and García Leiva, 2021; Iordache, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Netflix’s expansion strategy relies heavily on new content. Research into Netflix catalogues in Europe has shown that the large majority of their offerings still consist of Anglo-Saxon productions (EAO, 2020b; Iordache, 2021). Nevertheless, the data also shows a shift in the investments made in Netflix original content, which has become considerably more diverse in terms of language and country of origin, in the past years (Afilipoaie et al, 2021).…”
Section: Transnational Television: the Space Betweenmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is no longer possible to view Netflix as a single service operating under the same conditions in every media landscape; rather, Netflix should be apprehended as a federation of national services tied together in one platform (Lobato, 2018; Lobato and Lotz, 2020). In this regard, Netflix’s transnational expansion is understood as a multisided process of localisation whereby the more the company’s global audience grows, the more differentiated its programming, organisation and corporate infrastructures become (Iordache, 2021).…”
Section: The Global Age Of Netflix: a (R)evolution For Television?mentioning
confidence: 99%
“…Simultaneously Netflix has expanded its services to most international markets, with the company currently projecting to reach over 40 million global viewers by 2023, a strategy relying especially on investing in local productions not only for local audiences but for global distribution (Reuters, 2022). Such demand has led to both advantages and challenges for European producers (Iordache, 2021). Dominant platforms like Netflix can simultaneously perpetuate cultural homogeneity through purchasing and commissioning decisions and increase diversity by providing series like Dark (2017Dark ( -2020 and La casa de papel (2017-2021) much more globalised visibility (partially enforced by the European Union's requirements for a 30% of subsidised European content; Rankin, 2018).…”
Section: Introduction: the Increasingly Global Demand For High-end Tv...mentioning
confidence: 99%